Thinglink: An Alternative Platform to Make Students’ More Involved In Online Class during Covid-19 Pandemic - Darul Lailatul Qomariyah; Adip Arifin; Ratri Harida (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2023)
As the Corona virus pandemic occurs, the teaching and learning process at school runs in online. One of the teacher efforts is the use of digital tools, for example, Google Classroom, E-Learning, ThingLink, Quizizz, Quipper, and others. The function of this research is to know how the application of ThingLink is able to increase the students’ engagement get participated networked English teaching and learning during Covid-19 pandemic. The approach taken is qualitative. Observation and questionnaire were used as tools for collecting the data. The results of analysis were as follow: (1) The regular English online teaching and learning by the use of WhatsApp had some problems to the students. (2) The use of ThingLink creates enjoyable learning, managable time, accessible outside of school hours. By the use of ThingLink collaborated with WhatsApp to communicate among tutor and all pupils, made the online learning environment more vary and active. (3) The teacher uses ThingLink to Increase the students’ engagement in online English teaching and learning with steps: preparation, logging into the website, create, and share. To be concluded that the use of ThingLink can increase the students’ engagement in online English teaching and learning since the students’ perception that the use of ThingLink is very interesting, motivated, comfortable, not bored, effectively to use, and assist them to learn English either along the course or outside.